THE INFLUENCE OF FAMILY EDUCATION TYPES ON THE FORMATION OF CHILDREN’S ANXIETY AND AGGRESSION - Arakelyan, A. D.; Karapetyan, A. S. (Modern Psychology, 2021)
The article discusses the issues of anxiety and aggression, the relationship between types of family education.The article presents the results of a research conducted with primary school children and their parents.The results of the correlation between the types of family education, anxiety and aggression are presented, the peculiarities of the relationship are analyzed. According to the results of the research, over-care, harsh upbringing, change of types of education, cinderella types and authoritative style influence on the anxiety of a primery school children. Rigid education, changes in education typesandovercare influence on the aggressiveness of primary school children.